2009
DOI: 10.1213/ane.0b013e31819a85ae
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Response After Severe Subarachnoid Hemorrhage Related to Sodium and Blood Volume Regulation

Abstract: After severe SAH, in the context of multiple clinical interventions, increased natriuresis and low blood volume are consistent with cerebral salt wasting syndrome, probably related to the sequence of severe SAH, highly increased sympathetic tone, hyperreninemic hypoaldosteronism syndrome, and increased natriuretic peptides release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 43 publications
1
43
1
Order By: Relevance
“…The findings of our investigation are consistent with evidence in the literature linking sympathetic function with diverse systemic and multiorgan derangements, including hypertension [46], myocardial ischemia [47], congestive heart failure [48], cardiac tachyarrhythmias [49], sudden cardiac mortality [50], abnormal renal natriuresis [51], enhanced platelet aggregation [52] and impaired immune function [53]. Sympathetically mediated neurogenic cardiopulmonary complications have been related to adverse outcomes following SAH [54], and sympathetic activity has been connected to increased inflammation and enhanced thrombosis [7,8], the markers of which predict detrimental outcomes in patients with SAH [18,20].…”
Section: Discussionsupporting
confidence: 90%
“…The findings of our investigation are consistent with evidence in the literature linking sympathetic function with diverse systemic and multiorgan derangements, including hypertension [46], myocardial ischemia [47], congestive heart failure [48], cardiac tachyarrhythmias [49], sudden cardiac mortality [50], abnormal renal natriuresis [51], enhanced platelet aggregation [52] and impaired immune function [53]. Sympathetically mediated neurogenic cardiopulmonary complications have been related to adverse outcomes following SAH [54], and sympathetic activity has been connected to increased inflammation and enhanced thrombosis [7,8], the markers of which predict detrimental outcomes in patients with SAH [18,20].…”
Section: Discussionsupporting
confidence: 90%
“…In several uncontrolled studies, the development of volume contraction was found to be ameliorated by the administration of large amounts of fluids [17,19]. In another study, however, only hyponatremia but not decreased circulating blood volume was prevented by administration of large amounts of sodium and water, adapted to renal excretion [20]. The guidelines of the American Heart Association [21] recommend that volume contraction be treated with isotonic fluids (Class IIa, Level of Evidence B), and that ''administration of large volumes of hypotonic fluids should generally be avoided after SAH (Class I, Level of Evidence B)''.…”
Section: Discussionmentioning
confidence: 99%
“…There have been four prospective studies in adult neurosurgical patients where extracellular volume (ECV) was assessed by the gold standard method of radioisotope dilution [12][13][14][15]. In these studies over 50% of the patients had decreased ECV, supporting a diagnosis of CSW rather than SIAD.…”
Section: Cerebral Salt-wasting Syndromementioning
confidence: 99%
“…In these studies over 50% of the patients had decreased ECV, supporting a diagnosis of CSW rather than SIAD. In one study by Audibert et al, the development of hyponatremia was prevented in 19 patients with SAH by the prophylactic administration of 0.9% sodium chloride, yet 53% had decreased ECV, demonstrating that CSW can be common in neurosurgical patients and that hyponatremia is not a necessary feature [15]. Similar prospective studies with ECV measurements have not been conducted in children, but retrospective studies in children with CNS disease suggest that CSW may be as common as SIAD [16].…”
Section: Cerebral Salt-wasting Syndromementioning
confidence: 99%